2020
DOI: 10.1080/23779497.2020.1814162
|View full text |Cite
|
Sign up to set email alerts
|

Yemen: the challenge of delivering aid in an active conflict zone

Abstract: Introduction: In March 2015 a Saudi-led coalition began an air campaign and ground offensive in Yemen. The conflict has resulted in at least 100,000 people killed and 3.2 million people internally displaced. Over the last 29 months of the war, the Yemen Relief and Reconstruction Foundation (YRRF), working through an informal network of indigenous volunteers, has successfully provided food, clothing, medicine and water filters to areas under siege. Context: Asymmetric warfare complicates humanitarian assistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The spill threatens to disrupt nearly all of Yemen's Red Sea fisheries, which would worsen food security and exacerbate Yemen's displacement crisis as workers seek new employment [7][8][9]19 . Imports of medical supplies from aid groups would probably also be disrupted, further destabilizing health services 22,24 . Our modelling indicated that clean-up would be slow even under optimistic conditions; actual clean-up efforts would potentially be further prolonged and logistically difficult given the conflict in the region and sea mines in the water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spill threatens to disrupt nearly all of Yemen's Red Sea fisheries, which would worsen food security and exacerbate Yemen's displacement crisis as workers seek new employment [7][8][9]19 . Imports of medical supplies from aid groups would probably also be disrupted, further destabilizing health services 22,24 . Our modelling indicated that clean-up would be slow even under optimistic conditions; actual clean-up efforts would potentially be further prolonged and logistically difficult given the conflict in the region and sea mines in the water.…”
Section: Discussionmentioning
confidence: 99%
“…The data we use to model the spill and downstream effects are of variable quality, so our results may be affected by measurement error. Stored quantities of supplies could mitigate shortages in the event of port disruption, but such quantities are probably minimal as Yemen is already undergoing supply shortages, and price spikes would render supplies inaccessible for many 5,24 . Our model considers only the scenario of a full spill; we do not model, for example, the impacts of a minor leak in the hull.…”
Section: Discussionmentioning
confidence: 99%
“…Stored quantities of supplies could mitigate shortages in the event of port disruption, but such quantities are likely minimal as Yemen is already undergoing supply shortages, and price spikes would render supplies inaccessible for many. 5,24 Our model only considers the scenario of a full spill; we do not model, for example, the impacts of a minor leak in the hull. We do not provide expected durations for port and desalination plant closures since we are unable to predict the timing of cleanup efforts.…”
Section: Discussionmentioning
confidence: 99%
“…modeling24-hour spills and 72-hour spills during different seasons, we also modeled air pollution with and without combustion. For estimates of air pollution from combustion, we added the burned oil to particulate matter conversion rate from Middlebrook et al to the existing evaporative conversion rate.…”
mentioning
confidence: 99%
“…The poor human security situation in Yemen has encouraged international participation and aid into the country. Unfortunately, it is challenging to facilitate such assistance due to the civil war in Yemen (Fink, 2017;Kimball & Jumaan, 2020). The domestic situation devastated by war and the lack of health facilities (Garber et al, 2020;Sowers & Weinthal, 2021) has exacerbated the COVID-19 pandemic (International Rescue Committee, 2020).…”
mentioning
confidence: 99%